(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: The hospitality industry has undergone a sea change in the last decades. Some of the changes include competitive pressures, shifting consumer preferences and consumption patterns, technological advances and new distribution channels. Continuous renewal and adaptation are required to stay in business. The cry ‘Create, innovate or die!’ is a common phrase used by today’s managers. Objective: To identify the innovative technological advancements which can be incorporated in rooms, their acceptance by guests and to highlight the varied technological positive and negative impact on creating guest experience Methodology: Survey method through a questionnaire was primarily used for research. The study was conducted in three leading star hotels of Kolkata and data was collected by questionnaire technique. The sample comprised of people from housekeeping and front office department and hotel guests. Results: The employees were found to be aware and sensitized about the concept of latest innovations in hotel rooms which will benefit them as well as the industry in the long run. Conclusion: The study indicates that the hotels can include the latest innovations and technological advances in detail in rooms, which would be visionary for the hotels which are existing and upcoming in the near future without a doubt as these are the future of smart hotel features.